Middle-ear or mastoid granulation pathology associated with retraction of the pars flaccida and low-pitched tinnitus. Issue 4 (24th April 2021) - Lou, Z
Abstract: Objective: This study aimed to evaluate the clinical features and outcomes of patients with middle-ear granulation pathologies associated with attic retractions. Method: The clinical records of adult patients with middle-ear granulation pathologies and attic retractions confirmed via computed tomography and surgical exploration between January 2012 and January 2019 were retrospectively reviewed. Results: A total of 59 patients were included. Endoscopic examination showed a normal pars tensa but retraction of the pars flaccida in all patients. No granulation tissue or debris were observed. Low-pitched tinnitus was the principal complaint of 55 patients (100 per cent), followed by ear fullness (14 patients, 23.7 per cent). Of the 59 patients, 52 patients (88.1 per cent) underwent canal wall up mastoidectomy and 7 patients (11.9 per cent) underwent endoscopic endaural atticoantrotomy. No ossicular chain destruction was evident. All patients were followed up for 12 months. Tinnitus disappeared completely in 48 patients (81.4 per cent), improved significantly in 9 patients (15.3 per cent) and improved mildly in 2 patients (3.3 per cent). Conclusion: A granulation tissue pathology should be considered when a patient complains of low-pitched tinnitus and exhibits retraction of the pars flaccida. Computed tomography and surgical exploration should be scheduled.